The Copyright Wars: Three Centuries of Trans-Atlantic Battle - Peter Baldwin (Princeton University Press, 2021)
Today’s copyright wars can seem unprecedented. Sparked by the digital revolution that has made copyright—and its violation—a part of everyday life, fights over intellectual property have pitted creators, Hollywood, and governments against consumers, pirates, Silicon Valley, and open-access advocates. But while the digital generation can be forgiven for thinking the dispute between, for example, the publishing industry and Google is completely new, the copyright wars in fact stretch back three centuries—and their history is essential to understanding today’s battles. The Copyright Wars—the first major trans-Atlantic history of copyright from its origins to today—tells this important story. Peter Baldwin explains why the copyright wars have always been driven by a fundamental tension. Should copyright assure authors and rights holders lasting claims, much like conventional property rights, as in Continental Europe? Or should copyright be primarily concerned with giving consumers cheap and easy access to a shared culture, as in Britain and America? The Copyright Wars describes how the Continental approach triumphed, dramatically increasing the claims of rights holders. The book also tells the widely forgotten story of how America went from being a leading copyright opponent and pirate in the eighteenth and nineteenth centuries to become the world’s intellectual property policeman in the late twentieth. As it became a net cultural exporter and its content industries saw their advantage in the Continental ideology of strong authors’ rights, the United States reversed position on copyright, weakening its commitment to the ideal of universal enlightenment—a history that reveals that today’s open-access advocates are heirs of a venerable American tradition. Compelling and wide-ranging, The Copyright Wars is indispensable for understanding a crucial economic, cultural, and political conflict that has reignited in our own time.